2020
DOI: 10.20944/preprints202010.0353.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Multifaceted Roles of Copper in Cancer: a Trace Metal Element with Dysregulated Metabolism, but also a Target or a Bullet for Therapy

Abstract: In the human body, Copper (Cu) is a major and essential player in a large number of cellular mechanisms and signaling pathways. The involvement of Cu in oxidation-reduction reactions requires close regulation of copper metabolism in order to avoid toxic effects. In many types of cancer, variations in copper protein levels have been demonstrated. These variations result in increased concentrations of intra-tumoral Cu and alterations in the systemic distribution of copper. Such alterations in Cu homeostasis may … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 124 publications
(148 reference statements)
1
24
0
Order By: Relevance
“…Consistent with our reports, Cu concentration was also found to increase in tumor areas and even correlated with the grade of cancer [34][35][36]. High serum Cu levels were also found in cancer patients resistant to chemotherapy compared to patients responding to treatment [36] and promote the scatter and formation of secondary tumors by activating cell proliferation-related enzymes [23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our reports, Cu concentration was also found to increase in tumor areas and even correlated with the grade of cancer [34][35][36]. High serum Cu levels were also found in cancer patients resistant to chemotherapy compared to patients responding to treatment [36] and promote the scatter and formation of secondary tumors by activating cell proliferation-related enzymes [23].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies suggested aberrant copper homeostasis (ACH) was highly associated with cancers such as bladder cancer, breast cancer, colorectal cancer, and prostate cancers [19][20][21][22]. Supporting this, in carcinogenesis, ACH was observed to contribute to the proangiogenic response via various molecular pathways, which played a fundamental role in cancer proliferation or angiogenesis [23]. Moreover, copper accumulation in cancer cells was also reported [24,25].…”
Section: Discussionmentioning
confidence: 82%
“…5 ). Many cancer types are associated with aberrantly elevated levels of copper in patient serum ( 4 , 80 ), where this metal nutrient regulates several proteins involved in tumor growth and proliferation ( 4 , 81 ). Our findings show that changes in copper oxidation state are also important to consider in these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cu metabolism needs to be strictly controlled to prevent various diseases, including metabolic syndrome [21]. Absolutely, disordered Cu homeostasis can lead to a wide variety of cancers, including BRCA, colorectal cancer, and prostate cancer [22]. Several studies suggested that Cu was equipped to activate the mitogen-activated protein kinase (MAPK) pathway and facilitated tumorigenesis and cancer growth [23].…”
Section: Discussionmentioning
confidence: 99%